Pemberdayaan Masyarakat melalui Bazar Murah dan Kelas Ceria dalam Bidang Pendidikan dan Sosial - Ondy (Edujavare Publishing, 2024)
Mentoring activities aim to increase public awareness about social issues and develop students' abilities in creating creative Public Relations campaigns, while forming children's character through the Ceria Class and strengthening solidarity between Communication Science students at UBSI. The Bina Sarana Informatika University (UBSI)